Association between arterial stiffness, carbamylation, and mortality in patients undergoing coronary angiography with no or mild chronic kidney disease - Daschner, Clara; Kleber, Marcus E.; Stach-Jablonski, Ksenija; Yücel, Gökhan; Husain-Syed, Faeq; Ayasse, Niklas; Berg, Anders H.; März, Winfried; Krämer, Bernhard; Yazdani, Babak (Cardiorenal Medicine, 2025)
Introduction: The processes of atherosclerosis, inflammation, and carbamylation are closely linked in cardiovascular (CV) disease, but the potential of carbamylation burden as a CV mortality predictor is unclear, especially in patients with no or mild chronic kidney disease (CKD). This study aimed to investigate whether elevated carbamylated albumin (C-Alb), as a surrogate marker for carbamylation burden, is associated with mortality and arterial stiffness/atherosclerotic burden in patients with no or mild CKD, using pulse pressure (PP) as a marker for arterial stiffness. Methods: We measured C-Alb in 3,193 participants of the Ludwigshafen Risk and Cardiovascular Health study who had been referred for coronary angiography and followed up for 10 years. Results: The mean age was 62.7 years, and 30.4% were female. Mean blood pressure was 141/81 mm Hg, and mean C-Alb was 5.54 mmol/mol. Increase in C-Alb levels was associated with older age; female sex; increased PP, high-sensitivity C-reactive protein, and interleukin-6 levels; and increased incidence of coronary artery disease (CAD), peripheral artery disease (PAD), and carotid stenosis. In contrast, BMI, diastolic blood pressure (DBP), albumin, and the proportion of active smokers decreased with increasing C-Alb levels. In particular, C-Alb showed a highly significant correlation with CAD severity: Friesinger (Pearson correlation coefficient [r] = 0.082, p < 0.001) and Gensini score (r = 0.066, p < 0.001). The area under the curve (AUC) for all-cause mortality prediction by the European Society of Cardiology Heart Score (ESC-HS) significantly improved from 0.719 to 0.735, and the AUC for CV mortality prediction based on C-Alb increased from 0.726 to 0.750 in patients without previously known CV disease. C-Alb correlated directly and significantly with PP (r = 0.062, p < 0.001), which was consistently the strongest predictor of mortality across all C-Alb tertiles. The hazard ratios (HRs) for all-cause mortality per 10 mm Hg increase (or 1,000 mm Hg/min increase for double product [DP]) in the 1st tertile of C-Alb were 1.18, 1.13, 1.11, and 1.11 for PP, mean arterial pressure (MAP), systolic blood pressure (SBP), and DP, respectively, but the HR for DBP did not reach significance. In the 3rd tertile of C-Alb, the HRs were 1.13, 1.05, and 1.09, for PP, SBP, and DP, respectively, but the HR for MAP did not reach significance. Conclusion: C-Alb may be a valuable biomarker for assessing CV risk and improving mortality prediction even in patients with no or mild CKD. The findings support the notion of a crosslink between carbamylation, inflammation, atherosclerosis, and mortality. While these results are promising, further research is needed to fully elucidate the role of C-Alb in CV disease progression and risk stratification.